Reliability and reproducibility of macular segmentation using a custom-built optical coherence tomography retinal image analysis software - Cabrera DeBuc, Delia; Somfai, Ga´bor Ma´rk; Ranganathan, Sudarshan; Ta´trai, Erika; Ferencz, Ma´ria; Puliafito, Carmen A (Journal of Biomedical Optics, 2009)
We determine the reliability and reproducibility of retinal thickness measurements with a custom-built OCT retinal image analysis software (OCTRIMA). Ten eyes of five healthy subjects undergo repeated standard macular thickness map scan sessions by two experienced examiners using a Stratus OCT device. Automatic/semi automatic thickness quantification of the macula and intraretinal layers is performed using OCTRIMA software. Intraobserver, interobserver, and intervisit repeatability and reproducibility coefficients, and intraclass correlation coefficients (ICCs) per scan are calculated. Intraobserver, interobserver, and intervisit variability combined account for less than 5 of total variability for the total retinal thickness measurements and less than 7 for the intraretinal layers except the outer segment/ retinal pigment epithelium (RPE) junction. There is no significant difference between scans acquired by different observers or during different visits. The ICCs obtained for the intraobserver and intervisit variability tests are greater than 0.75 for the total retina and all intraretinal layers, except the inner nuclear layer intraobserver and interobserver test and the outer plexiform layer, intraobserver, interobserver, and intervisit test. Our results indicate that thickness measurements for the total retina and all intraretinal layers (except the outer segment/RPE junction) performed using OCTRIMA are highly repeatable and reproducible.